Zur Implementation der Produktverantwortung bei der Altautoentsorgung: Kostenerstattung statt Rücknahmeverpflichtung? - Markus A. Lehmann (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2001)
– This paper compares two instruments for implementing producer responsibility for used cars. The German regulatory solution, relying on take-back obligations for producers, free for the last holder, is contrasted with a rule of partial cost recovery. It is shown that the cost-recovery rule saves infra-strucure costs and avoids the anti-competitive impacts of the take-back obligation. In contrast to the take-back obligation, the cost-recovery rule makes it possible to optimize between the environmental and competition policy objectives, and it can thus defuse the alleged tradoff between these policy areas. This paper concludes by giving a mixed judgement on the European Guideline.
Keywords: 330; Gebrauchtfahrzeug; Abfallentsorgung; Kreislaufwirtschaft; Abfallrecht; Kompensationsmaßnahme; Theorie; Deutschland